Dose Effect of NPK Mutiara and Dolomite At Plant Nursery Oil Palm (Elaeis quineensis Jacq) In Main Nursery: Pengaruh Dosis Pupuk NPK Mutiara dan Dolomit Pada Pembibitan Tanaman Kelapa Sawit (Elaeis quineensis Jacq) Di Main Nursery - Rusdi; Tutik Nugrahini; Purwati (Universitas Widya Gama Mahakam, 2015)
Dose Effect of NPK Mutiara and Dolomite At Plant Nursery Oil Palm (Elaeis Jacq quineensis) In Main Nursery. The purpose of this study to determine the Pearl NPK fertilizer and lime Dolomite as well as interactions between NPK fertilizer and lime Dolomite Pearl the best. The study was conducted over six months, starting in April 2010 to September 2010. The location of research at Nursery Gardens Pilot Program Crops Cultivation Agricultural Polytechnic State Samarinda. Research arranged in a randomized block design (RAK) with 2 x 3 factorial experiment as much as 6 times the number of replications. The first factor is the granting Lime Dolomite (D) comprising, namely: d1 = 5 g / staple crops, d2 = 10 g / staple crops. The second factor is the Pearl of NPK fertilizer consists of three levels, namely: m1 = 5 g / staple crops, m2 = 10 g / staple crops, m3 = 15 g / staple crops. The results showed the treatment of lime Dolomite significant effect on the parameters diameter hump month 1, but does not affect the measurement of the diameter of the stump month 2 to month 6, and did not significantly affect the number of parameters midrib, and did not affect the parameters plant height. Effect of NPK Mutiara best to the growth of oil palm seedlings in the nursery play is achieved by treatment of m2 (NPK Mutiara 10 g / staple crop). The results showed the interaction between Dolomite Lime and NPK Mutiara significantly affect the number of midrib, stump diameter and plant height. Interaction between NPK best dose Pearl and Lime Dolomite (DXM) for the growth of oil palm seedlings in the nursery play is achieved by treatment (d2m2) Dolomite lime is 10 g / staple crop NPK Mutiara + 10 g / staple crops. Keywords: NPK Mutiara, Dolomite and oil palm Plant